First Asian report of the genus Chilibathynella Noodt, 1963 (Bathynellacea, Syncarida), with the description and biogeographic significance of a new species from Kotumsar Cave, India - Reddy, Y. Ranga (Zootaxa, 2006)
The gen us Chilibathynella Noodt , 1963, presently contains two species: C. clandestina Noodt, 1963 and C. australiensis Schmi nke, 1973, fr om Central Chile an d southe r n Australia, respectivel y. A third spe cies, nam ed Chilibathynella kotumsarensis n. sp., is described herein f r om a cave in India. Th e new species has a unique combi n ation o f morphological cha r acters , which, inter alia, include six-segme nted anten na, presence of epip odite on th oraco pod I and of three en dopodal setae on the male thor acopod VIII , inhomonomous row o f spines on uro podal s ymp od, spineless uropod al endopodite, and convex anal operculu m. Some of these characters have not only necessitated pa r tial amendment of the generic diagnosis , but could p r ove of value in phylogenetic studies as well . Furthermore , the discovery of the new species is of interest because it is the first r ecor d of Chilibathynella from Asia as well as the tropical zone , thus filling a huge gap in the global distrib ution of t his genus.